2001
DOI: 10.2307/3345711
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Music Teachers' Conceptions of Teaching Effectiveness, Microteaching Experiences, and Teaching Performance

Abstract: Fifteen undergraduate music education majors who were enrolled in an introductory music education course constructed concept maps on the topic of “teacher effectiveness” prior to and following two microteachings. The Survey of Teaching Effectiveness (STE) and a time sampling procedure based on criteria from teacher-intensity (TI) research measured teaching performance. Conceptions of teaching effectiveness were examined from two perspectives: cognitive structure, measured by map scores, and conceptual understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 11 publications
7
48
1
3
Order By: Relevance
“…Students indicated that microteaching experience was an enjoyable experience as it offered them opportunities to increase self-confidence in discovering and enhancing their teaching skills and language ability. Similarly, Butler (2001) reported that student teachers viewed microteaching as a highly beneficial activity, preparing them for the "real classroom" practice. In addition, in a relevant study about the effect of microteaching application on preservice teachers" competency levels, Karckay and Sanli (2009) reported a result confirming that microteaching may affect students" teaching competency.…”
Section: Microteaching Often Allows Us To Use Information and Theoriementioning
confidence: 99%
See 1 more Smart Citation
“…Students indicated that microteaching experience was an enjoyable experience as it offered them opportunities to increase self-confidence in discovering and enhancing their teaching skills and language ability. Similarly, Butler (2001) reported that student teachers viewed microteaching as a highly beneficial activity, preparing them for the "real classroom" practice. In addition, in a relevant study about the effect of microteaching application on preservice teachers" competency levels, Karckay and Sanli (2009) reported a result confirming that microteaching may affect students" teaching competency.…”
Section: Microteaching Often Allows Us To Use Information and Theoriementioning
confidence: 99%
“…Generally, students bring their academic experiences and expectations to the classroom and they are, to some extent, expecting teachers to comply with them. Initially, educators and teacher trainers should try to understand what preconceptions student teachers are bringing with them to their microteaching experiences in order to help them acquire essential instructional knowledge and enhance effective teaching techniques (Butler, 2001). Another study by Amobi and Irwin (2009) also provided evidence that students in teacher training programs have some kind of knowledge about the art of teaching gained by different means.…”
Section: Microteaching Often Allows Us To Use Information and Theoriementioning
confidence: 99%
“…A more complete understanding of how pre-service teachers acquire conceptions of effective teaching may enable teacher educators to develop more efficient and effective teacher training programmes (Hash 2010;Butler 2001). Programmes that require teacher candidates to submit reports or portfolios containing lesson plans, student observations, reflections on student progress, and self-evaluations can help them and their supervisors identify and better understand successful practice and problem areas.…”
Section: Discussionmentioning
confidence: 98%
“…Düşünme süreçlerinin ve etkinliklerin gerçekleştirilmesinin bir sonucu olarak ortaya çıkan Ana Safhalar bölümü ise beş evreden oluşur: öğretmen adayının düşünme süreçlerini, farklı yöntem ve teknikleri kullanarak nasıl bir ön hazırlık yapacağını ve sunumunun içeriğini belirlediği karar verme evresi; içerik, sergilenecek öğretim davranışları ve diğer öğretmen adaylarının önerileri göz önünde bulundurularak öğretim plan ve materyallerinin hazırlandığı planlama evresi; öğretmen adayının hazırladığı plana göre sunumunu yaptığı diğer öğretmen adayları ve ders sorumlusunun gözlemlerini not ettikleri uygulama evresi; birisi sunumdan hemen sonra diğeri de bütün sunumlardan sonra yapılan iki değerlendirmeyi içeren değerlendirme evresi ve sunum yapan öğretmen adaylarının etkinliklerinin her aşamasında akranları ve öğretim elemanından aldıkları geri bildirimlere dayalı kararları kapsayan yansıtma evresi. Mikro-öğretim ile ilgili alan yazın incelendiğinde tekniğin farklı alanlardan öğretmen adaylarının öğretmenlik becerilerini geliştirmeye etkisini inceleyen çok sayıda çalışma olduğu saptanmıştır: Bayraktutar, 1994;Benton-Kupper, 2001;Butler, 2001;Erökten ve Durkan, 2009;Görgen, 2003;Gürses, Bayrak, Yalçın, Açıkyıldız ve Doğar, 2005;Kılıç, 2010;Kpanja, 2001;Kuran, 2009;Küçükoğlu, Köse, Taşgın, Yılmaz ve Karademir, 2012;Külahçı, 1994;Meral ve Zerayak, 1999;Peker, 2009;Sarı, Sakal ve Deniz 2005. Ancak yabancı dil eğitiminde mikroöğretim uygulamalarına dair alan yazın incelendiğinde az sayıda çalışmaya rastlanmıştır: Çakır ve Aksan 1992; Ekşi 2012.…”
Section: Introductionunclassified